Explore The Mid-day Meal Policy in the Context of Retention in School Education (Pragyaratna प्रज्ञारत्न, 2024)
Explore The Mid-day Meal Policy in the Context of Retention in School Education: A Teacher's Perspective from Lalitpur District. Nepal's midday meal policy, aimed at improving children's health and educational access, is a critical component of its national education system. However, limited research has explored this policy from the viewpoint of community school teachers. This study addresses three pivotal research questions: The funding for midday meals is adequate. The allocated funding is fully utilized. The program enhances education quality and reduces dropout rates due to midday meals. In-depth interviews with Lalitpur district teachers, where the midday meal policy is active, provided qualitative data. Ethical considerations safeguarded participants' identities and opinions. Teachers expressed concerns about insufficient funds for midday meals, requiring additional local contributions. Nevertheless, they reported that the granted funds were fully utilized, supporting students' nutrition and local farmers. The program positively impacted education quality and reduced dropout rates. This study underscores the midday meal policy's challenges and successes, highlighting the importance of supplementary financial support for student nutrition. It also emphasizes the program's multiple advantages, including improved education quality and lower dropout rates, especially among disadvantaged students. The provision of a midday meal program in schools can have a positive impact on student retention This research offers vital insights into Nepal's midday meal policy's impact on the education system. It emphasizes the ongoing need for financial support to sustain and enhance the program, ultimately benefiting children's comprehensive development.